Overhang analysis fabricated using fused deposition modelling technique - Mazlan, Siti Nur Humaira; Abdul Kadir, Aini Zuhra; Yusof, Yusri; Wahab, Md Saidin (UTHM Publishing, 2020)
Additive manufacturing (AM) is a process using layer by layer additive technique to fabricate the entire 3D models into a functional component. One of the most popular AM technology is fused deposition modeling (FDM) that utilizes thermoplastic filaments as the materials. AM has the ability to produce complex structure easily without additional tool and fixture, therefore, it can save the overall manufacturing process. However, without optimum design and parameter settings, FDM has a limitation in printing overhang structures. Therefore, this study aims to analyze three types of pass-fail overhang features which are draft angle, overhang length and overhang angle varied accordingly to their respective length and angle. These pass-fail features were fabricated using the FDM 3D printer with standardized 3D printing parameters. The dimensional accuracy of these features was evaluated using an image analyzer. The results showed that the allowable overhang length to be produced is starting from the length of 0.5 mm to 1.5 mm. Meanwhile, for the draft and overhang angles, the allowable angle to be produced is ≥ 50.00 mm and ≤ 45.00 mm, respectively. From this study, it highlights the limitations of the overhang pass-fail features and provide the designer with the design information to help them designing the optimal design solution using FDM.